IMPLEMENTASI PENDEKATAN CULTURALLY RESPONSIVE TEACHING (CRT) DENGAN MENGGUNAKAN PODCAST DI SPOTIFY UNTUK MENINGKATKAN KEMAHIRAN MENYIMAK TEKS BERITA PADA SISWA KELAS VII.3 SMP NEGERI 10 TANJUNGPINANG - Nadila Angelina Nadila; Harry Andheska; Gigih Harpuas (Fakultas Bahasa dan Sastra Universitas PGRI Kanjuruhan Malang, 2025)
This study aims to enhance the listening comprehension of seventh-grade students (Class VII.3) at State Junior High School 10 Tanjungpinang through the implementation of a Culturally Responsive Teaching (CRT) approach using podcasts on Spotify. The CRT framework was employed to address the monotony of conventional instructional media and to increase student engagement by incorporating content that resonates with their cultural background. This classroom action research was conducted over two cycles. The results indicate a significant improvement in students’ listening comprehension: the average pretest score of 63 rose to 86 following the Cycle I podcast intervention. Podcasts proved to be a flexible and engaging learning medium that also encouraged students to think critically about the information presented. Furthermore, the teacher’s role in fostering an inclusive learning environment contributed to the success of this approach. These findings suggest that CRT‑based podcast integration offers an innovative solution for teaching listening comprehension.